Melestarikan Indigenous Knowledge (IK) Melalui Pengelolaan Koleksi Langka di Perpustakaan - Dyah Ayu Kusuma Dewandaru (Media Informasi, 2023)
Rare collections are a source of information that has an important position in libraries. This collection contains various information related to culture, customs and traditions sourced from ancient texts and manuscripts. It is created by human civilization which are products of traditional knowledge or is called Indigenous Knowledge (IK). This collection is documented so that its information value can continue to flow from generation to generation. The high value of information contained in rare collections places them as a source of reference and research material for researchers and public. Libraries need to manage and preserve these collections so that they can be utilized optimally. This paper aims to describe the various stages in managing and preserving IK in rare collections. The method used is literature study to answer the problems. The results of the analysis show that the stages of management and preservation of IK in rare collections consider the following steps: 1) libraries need to develop policies for collection development and preservation; 2) the library considers the existence or placement of the collection; 3) the nature, form, or format of the collection; 4) physical preservation; and 5) challenges and opportunities and that can be considered in collection management.